Less words, more action trainer's manual. how to increase women's participation in leadership and decision-making in co-operatives. - Asian Women in Cooperative Development Forum; International Cooperative Alliance. Regional Office for Asia and Pacific (Quezon City Asian Women in Co-operative Development Forum, 1999)
A trainer's manual that highlights information and proper teaching of women's problems leadership marginalization in co-ops. It is intended for use by trainers, field workers and community organizers close to members of co-ops at the grassroots level. The manual contains many illustrations and "Note to trainer" guides to help facilitate better delivery of ideas.
Jointly published by International Co-operative Alliance Regional Office for Asia and Pacific.
Keywords: Women in cooperative societies -- Handbooks, manuals, etc; Leadership in women -- Handbooks, manuals, etc